PERSEPSI PETANI TERHADAP TEKNOLOGI PENYIMPANAN BAWANG PUTIH (Allium sativum L) DI KABUPATEN MAGELANG - Fitri Lestari; Sri Catur Budi; Restu Hidayah; Dian Dini; Retno Endrasari (MEDIAGRO, 2020)
Garlic (Allium sativum L) is a horticultural product that can easily be damaged if not handled properly. Damage that usually occurs in garlic includes softening of tubers, wrinkles, empty tubers, rot, sprouting, root growth and mold growth. Some of the familiar storage methods used by farmers include storage using pesticides and fumigation, while storage with ozone has only been introduced to farmers. Most of the farmers (84,44%) gave high perceptions of garlic storage technology using pesticides, 78.05% of farmers gave high perceptions of garlic storage technology with smoking and 60.25% of farmers gave moderate perceptions of garlic storage technology with ozone. In terms of ease of application, all farmers assessed storage with pesticides as easy to apply, storage with fumigation 96.77% of farmers considered it easy while the majority of farmers (63.33%) considered storage with ozone difficult to apply. This means that the majority of respondents are not too interested in using ozone technology for storing garlic. Ozone technology required a large investment to make closed storage without ventilation so ozone can work optimally, while now farmer's storage still simple and open. Keywords : garlic, ozon technology, perception